2015
DOI: 10.1002/ajim.22428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occupational exposure to carcinogens among workers of Arabic, Chinese and Vietnamese ancestry in Australia

Abstract: Knowing the prevalence of exposure to carcinogens in the workplace in different ethnic groups will allow better targeted and informed occupational health and safety measures to be implemented where necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
1
11
1
Order By: Relevance
“…Firstly, it is possible that the results may have been influenced by the translation method, as direct translation has lower validity and reliability than other translation methods (Weeks et al, 2007). Secondly, although our sample was broadly representative of the employed population of these ethnic groups in Australia several groups were under-represented, including younger people, people with no post-school qualifications, and immigrants (Boyle et al, 2015). The telephone listings-based sampling frame used in this study is one likely reason for the under-representation of these groups (Boyle et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Firstly, it is possible that the results may have been influenced by the translation method, as direct translation has lower validity and reliability than other translation methods (Weeks et al, 2007). Secondly, although our sample was broadly representative of the employed population of these ethnic groups in Australia several groups were under-represented, including younger people, people with no post-school qualifications, and immigrants (Boyle et al, 2015). The telephone listings-based sampling frame used in this study is one likely reason for the under-representation of these groups (Boyle et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Secondly, although our sample was broadly representative of the employed population of these ethnic groups in Australia several groups were under-represented, including younger people, people with no post-school qualifications, and immigrants (Boyle et al, 2015). The telephone listings-based sampling frame used in this study is one likely reason for the under-representation of these groups (Boyle et al, 2015). Thirdly, we used an area-level assessment of socioeconomic status rather than an individual level assessment, which may have resulted in some misclassification of socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically undocumented migrant farmworkers were more likely to work for a farm labour contractor rather than directly for a grower, were less likely to be aware of workers’ compensation rights, were less likely to have health insurance, and were more likely to use raiteros (informal and often expensive drivers) for transportation to and from worksites, than documented workers [Villarejo et al, ]. Other work has shown that migrant workers in a range of industries, irrespective of documentation status, have a higher incidence of occupational injuries and fatalities [Loh and Richardson, ], and exposure to workplace hazards [Boyle et al, ] than native‐born workers [Schenker ].…”
Section: Introductionmentioning
confidence: 99%
“…This concerns an earlier period of Australian history and is related to what occurred in the postwar period of the industrial development of Australia. However, the pattern may continue as recent work from 2013 showed disparities in exposure to occupational carcinogens among workers from Arabic, Chinese and Vietnamese ancestry compared with Australian workers 13. In particular, exposure to carcinogens was greater among those who completed a telephone interview in either Arabic, Mandarin, Cantonese or Vietnamese compared with those who completed the interview in English 22…”
Section: Discussionmentioning
confidence: 99%